Pilot cluster randomised trial of an evidence-based intervention to reduce avoidable hospital admissions in nursing home residents (Better Health in Residents of Care Homes with Nursing—BHiRCH-NH Study) - Katherine Froggatt; Rachael Hunter; Louise Marston; Louise Robinson; Greta Rait; John Young; Elizabeth L Sampson; Alexandra Feast; Alan Blighe; Brendan McCormack; Shirley Nurock; Monica Panca; et al. (BMJ Open)
Objectives To pilot a complex intervention to support healthcare and improve early detection and treatment for common health conditions experienced by nursing home (NH) residents.Design Pilot cluster randomised controlled trial.Setting 14 NHs (7 intervention, 7 control) in London and West Yorkshire.Participants NH residents, their family carers and staff.Intervention Complex intervention to support healthcare and improve early detection and treatment of urinary tract and respiratory infections, chronic heart failure and dehydration, comprising: (1) ‘Stop and Watch (S&W)’ early warning tool for changes in physical health, (2) condition-specific care pathway and (3) Situation, Background, Assessment and Recommendation tool to enhance communication with primary care. Implementation was supported by Practice Development Champions, a Practice Development Support Group and regular telephone coaching with external facilitators.Outcome measures Data on NH (quality ratings, size, ownership), residents, family carers and staff demographics during the month prior to intervention and subsequently, numbers of admissions, accident and emergency visits, and unscheduled general practitioner visits monthly for 6 months during intervention. We collected data on how the intervention was used, healthcare resource use and quality of life data for economic evaluation. We assessed recruitment and retention, and whether a full trial was warranted.Results We recruited 14 NHs, 148 staff, 95 family carers and 245 residents. We retained the majority of participants recruited (95%). 15% of residents had an unplanned hospital admission for one of the four study conditions. We were able to collect sufficient questionnaire data (all over 96% complete). No NH implemented intervention tools as planned. Only 16 S&W forms and 8 care pathways were completed. There was no evidence of harm.Conclusions Recruitment, retention and data collection processes were effective but the intervention not implemented. A full trial is not warranted.Trial registration number ISRCTN74109734 (https://doi.org/10.1186/ISRCTN74109734).Original protocol BMJ Open. 2019;9(5):e026510. doi:10.1136/bmjopen-2018-026510.